Perilaku Kepatuhan Wajib Pajak Orang Pribadi Terhadap Implementasi Coretax: Perspektif Behavioral Accounting Pada KPP Pratama Situbondo - Sara Maulina Putri; Putri Eva Ardianti; Ade Erawati; Nur Ika Mauliyah (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2026)
This study aims to analyse the compliance behaviour of individual taxpayers who are employees in relation to the implementation of the CoreTax Administration System (Coretax) using a behavioural accounting perspective. The method employed is a descriptive qualitative approach involving interviews, observations and documentation of taxpayers at the Situbondo Tax Office. The results of the study indicate that the implementation of Coretax has improved efficiency, effectiveness, and transparency in tax administration through system integration, automated reporting, and ease of data verification. The automation features within Coretax have also been shown to help improve the timeliness of reporting and reduce administrative errors. However, the level of taxpayer compliance is influenced not only by the system but also by behavioural factors such as understanding, trust, social norms, service quality, and perceptions of penalties. Therefore, the success of tax digitalisation must be supported by improved taxpayer literacy and awareness to foster sustainable compliance.